Legal Protection of Child Victims of Economic Exploitation in Makassar City: An Examination of the Child Protection Law and Islamic Law - Ismail, Khumaerah; Syamsuddin, Rahman; Irfan, Irfan (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
The aim of this research is to find out what forms of exploitation occur in the city of Makassar, what regulations are given based on UU No. 35 of 2014 and the views of Islamic law on the protection of children who are victims of exploitation. In conducting this research the author used a qualitative research method that focuses on in-depth observation with data collection using primary data by conducting interviews, documentation and observation, and secondary data in the form of literature reviews of books, journals and other references. The results of this research are various forms of exploitation that occur in the city of Makassar, among which the most frequently found are beggars, buskers, children selling, wearing costumes, etc. regarding the factors that cause this exploitation to occur, the main thing is the economy, as said by the resource person, how will they meet their daily needs if they don't do things like this, therefore the social service provides assistance every month to families in need so that their children can survive? Going to the street based on coercion or self-will can be minimized in one way or another in this way. Regarding the regulation of law number 35 of 2014 which discusses the prohibition of exploiting children economically and sexually and the sanctions provided are in the form of imprisonment for a maximum of 10 years and/or a fine of a maximum of 200,000,000 (two hundred million rupiah) this provision is contained in Article 76I Jo Article 88 of Law Number 35 of 2014 concerning the protection of children, but the reality is that most cases like this do not proceed to the pre-trial realm due to lack of evidence, therefore the RJ (Restroative justice) method is likely to be more effective in resolving the problem. From the perspective of Islamic law, it can be seen from the view of the maqasyidul sharia imam who discusses the need to look after children as someone who will be useful in the future. And regarding exploitation, in this case what is meant is street children who carry out begging activities, the MUI issued fatwa number 1 of 2021 concerning exploitation and begging activities on the streets. The main implication of this research lies in the awareness of the public as well as government institutions by providing education or by means of holding seminars or campaigns through schools, social media so that awareness regarding exploitation, its characteristics and how to report it can increase and strengthen strict law enforcement against the perpetrators involved.